Abstracts Accepted for Publication 2019
DOI: 10.1136/annrheumdis-2019-eular.4303
|View full text |Cite
|
Sign up to set email alerts
|

Ab0250 real-World Outcomes in Stable Originator Biologic-Treated Adult Patients Who Stayed on the Therapy Versus Those Who Switched to Biosimilar: A Retrospective Chart Review Study in Europe

Abstract: BackgroundBiologic therapies have considerably improved clinical management of autoimmune diseases. Over the past few years, several biosimilars have been introduced in Europe for these conditions. Limited information is available evaluating the impact of switching stable patients from originators to their respective biosimilars in clinical practice for non-medical reasons.ObjectivesThis real-world study reported and compared patient characteristics, clinical outcomes, and healthcare resource utilization (HRU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…It was found that, in comparison to non-switchers, patients who switched to the biosimilar experienced an increase in the number of various services at both 0–3 months and 4–6 months post-switch, which included blood tests, x-rays, ultrasounds, ER visits, specialist visits, and hospitalizations [ 32 ]. In line with these results, the studies by Gibofsky et al (2019) and Glintborg et al (2018) also found an increase, although marginal, in the number of outpatient visits post-NMS for rheumatology patients, including RA, psoriatic arthritis, and axial spondylarthritis [ 33 , 34 ]. The difference in outpatient visits for patients with rheumatic disease associated with NMS was greater in the study by Tarallo et al (an increase ranging from 0.18 to 0.70 over 3 months) in comparison to both Gibofsky et al and Glintborg et al (an increase of 0.2 over 3 months and 0.01 at 6 months post-switch vs 6 months pre-switch, respectively) [32 34 ].…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…It was found that, in comparison to non-switchers, patients who switched to the biosimilar experienced an increase in the number of various services at both 0–3 months and 4–6 months post-switch, which included blood tests, x-rays, ultrasounds, ER visits, specialist visits, and hospitalizations [ 32 ]. In line with these results, the studies by Gibofsky et al (2019) and Glintborg et al (2018) also found an increase, although marginal, in the number of outpatient visits post-NMS for rheumatology patients, including RA, psoriatic arthritis, and axial spondylarthritis [ 33 , 34 ]. The difference in outpatient visits for patients with rheumatic disease associated with NMS was greater in the study by Tarallo et al (an increase ranging from 0.18 to 0.70 over 3 months) in comparison to both Gibofsky et al and Glintborg et al (an increase of 0.2 over 3 months and 0.01 at 6 months post-switch vs 6 months pre-switch, respectively) [32 34 ].…”
Section: Resultsmentioning
confidence: 67%
“…In line with these results, the studies by Gibofsky et al (2019) and Glintborg et al (2018) also found an increase, although marginal, in the number of outpatient visits post-NMS for rheumatology patients, including RA, psoriatic arthritis, and axial spondylarthritis [ 33 , 34 ]. The difference in outpatient visits for patients with rheumatic disease associated with NMS was greater in the study by Tarallo et al (an increase ranging from 0.18 to 0.70 over 3 months) in comparison to both Gibofsky et al and Glintborg et al (an increase of 0.2 over 3 months and 0.01 at 6 months post-switch vs 6 months pre-switch, respectively) [32 34 ]. Once again similar to Tarallo et al, the study by Glintborg et al (2018) reported a significant increase in the utilization of various healthcare resources, albeit different resources than those reported in Tarallo et al (2019), following infliximab NMS [ 33 ].…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations